Implementasi Metode Bercerita untuk Meningkatkan Kemampuan Literasi Anak Usia 7-12 Tahun di Perpustakaan Rungkut Surabaya: Implementation of Storytelling Methods to Improve Literacy Skills of Children Aged 7-12 Years at the Rungkut Library in Surabaya. - Tri Lestari; Desika Putri Mardiani (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2026)
The literacy crisis among elementary school children in Indonesia shows that reading ability is still limited to deciphering texts, without optimal contextual understanding. This condition is exacerbated by the dominant use of gadgets, which has shifted children's reading habits and social interactions. This study aims to analyze the implementation of storytelling as a dialogic literacy practice in a literacy ecosystem involving children, tutors, families, and the learning environment at the Rungkut Library in Surabaya. The research method used was a descriptive qualitative approach, involving in-depth interviews, participant observation, and documentation of six purposively selected informants. Data analysis used the interactive model of Miles, Huberman, and Saldana (2014). The results showed that storytelling activities create a dialogic space that allows children to engage in narrative reconstruction through interactions with tutors and peers, thereby constructing meaning together through the communication process. The 5W+1H approach and story retelling have been shown to improve children's reading comprehension, oral communication skills, and self-confidence. Family involvement is a real supportive factor through the habit of storytelling at home, while excessive gadget use and inconsistent attendance are the main inhibiting factors. This study provides a conceptual contribution to storytelling as a social literacy practice in community-based non-formal education.